Exploring short-form video application addiction: Socio-technical and attachment perspectives. (September 2019) - Zhang, Xing; Wu, You; Liu, Shan
Highlights: This study examines the factors that affect short-form video app addiction. Social interaction anxiety and social isolation increases interpersonal attachment. Personalization and entertainment increases site attachment. Interpersonal and site attachments increase short-form video app addiction. Abstract: Short-form video applications (apps) have become increasingly popular in recent years. However, the excessive use of these apps can be addictive for certain individuals. This paper combined the socio-technical approach and attachment theory to build a holistic framework to study the factors that affected addiction to short-form video apps. In this study, 388 valid questionnaires were collected to test the hypotheses. Results corroborated that social interaction anxiety and social isolation were positively related to interpersonal attachment and that personalization and entertainment were positively related to site attachment. Interpersonal and site attachments had significant positive influences on short-form video app addiction. Moreover, neuroticism positively moderated the influence of social interaction anxiety on interpersonal attachment and positively moderated the influence of personalization on site attachment.